The complete idiot's guide to writing well - Rozakis, Laurie E. (Indianapolis, Indiana : Alpha Books, 2000)
From the author of The Complete Idiot's Guide to Grammar and Style, The Complete Idiot's Guide to Creative Writing, and The Complete Idiot's Guide to Shakespearce comes this primer for adults and students that instructs on the basics of writing. From contemporary, popular methods of communication, such as e-mail to Internet chat rooms, to more serious modes of writing, such as proposals, reports, and papers, this is the guide that can help anyone: formulate ideas, write with clarity and conciseness, focus on a thesis, create and structure a working outline, write a proper introduction and conclusion incorporate a broader vocabulary, construct magnificent sentences, develop smooth transitions and linear development of thought. Along the way, users of the book learn how to impress readers with clean, superlative writing that is free from embarrassing spelling errors, syntax mistakes, and redundancies. Includes ample writing samples, as well as the major dos and don'ts. Contents: Write now -- The writing process -- Write for success -- Just shoot me now: research papers and term papers -- More big deals -- Picture perfect.
Keywords: ENGLISH LANGUAGE -- RHETORIC -- PROBLEMS, EXERCISES, ETC